Brain–heart communication: Evidence for "central pacemaker" oscillations with a dominant frequency at 0.1 Hz in the cingulum. Issue 1 (January 2017) - Pfurtscheller, Gert; Schwerdtfeger, Andreas R.; Seither-Preisler, Annemarie; Brunner, Clemens; Stefan Aigner, Christoph; Brito, Joana; Carmo, Marciano P.; Andrade, Alexandre
Highlights: Differentiation between vascular and neural BOLD oscillations at ∼0.1 Hz. Central pacemaker in the midcingulum (∼0.1 Hz) modulates heart rate and contributes to heart rate variability (HRV). Indirect evidence of slow rhythmic neural activity changes in different brain regions. Abstract: Objectives: In the brain and heart, oscillations at about 0.1 Hz are conspicuous. It is therefore worthwhile to study the interaction between intrinsic BOLD oscillations (0.1 Hz) and slow oscillations in heart rate interval (RRI) signals and differentiate between their neural and vascular origin. Methods: We studied the phase-coupling with a 3T scanner with high scanning rate between BOLD signals in 22 regions and simultaneously recorded RRI oscillations in 23 individuals in two resting states. Results: By applying a hierarchical cluster analysis, it was possible to separate two clusters of phase-coupling between slow BOLD and RRI oscillations in the midcingulum, one representative for neural and the other for vascular BOLD oscillations. About half of the participants revealed positive time delays characteristic for neural BOLD oscillations and neurally-driven RRI oscillations. Conclusions: The results suggest that slow vascular and neural BOLD oscillations can be differentiated and that intrinsic oscillations (0.1 Hz) originate in the cingulum or its close vicinity and contribute to heart rate variability (HRV). Significance: The study provides new insights into the dynamics of resting state activities, helps to explain HRV, and offers the possibility to investigate slow rhythmic neural activity changes in different brain regions without EEG recording.